PSVI-22 Immunity indicators of calves obtained from cows with ketosis during the treatment process. (5th December 2019) - Kovalev, Sergey; Nikitina, Anastasia; Anipchenko, Polina; Stekolnikov, Anatoly; Kiselenko, Pavel; Alekhin, Yuiriy
Abstract: The purpose of these studies was to determine the indicators of cellular and humoral immunity of calves. Compared to calves obtained from untreated cows, the number of T-lymphocytes in young calves born from cows treated with Timolin increased the level of T-cells to 32.9%, while using Timosplenin 45%. As a result of the use of immunomodulators in treating cows with ketosis in mothers, the relative content of T-lymphocytes in the blood of calves born from them increased when using the drug Leucogen by 1.7 times, Timosplenin by 2.3 times, Timalin in 2.2 times. The use of Leucogen for cows with ketosis contributed to an increase in the percentage of B cells in the blood of calves born by 23%, Timosplenin 83%, and Timalin 42%. At the same time, the absolute number of B-lymphocytes in the treatment of "Leucogen" increased 1.9 times and reached the level of healthy calves, in the treatment with the preparations "Timosplenin" and "Timalin" - the increase was, respectively, 3.0 and 2.3 times and was higher this indicator in young animals born from healthy calves. Thus, the inclusion of dry immunomodulators in the treatment regimen of patients with ketosis leads not only to normalization of metabolism, but is also accompanied by an increase in the level of cellular immunity factors in calves born from them. Under the influence of "Leucogen, " the percentage of lymphocytes was normalized, whereas with the introduction of "Timalin" and "Timosplenin, " the content of this type of cells in newborn calves even exceeded those in healthy young.